Design of the crashworthy structure of an urban aircraft - Shang Bairong; He Jingwu; Xiong Yuexi; Hu Zhe (MATEC Web of Conferences, 2017)
With the development of general aviation, the urban aircraft is around the corner. The urban aircraft with composite is considered as an ultralight vehicle and the crashworthiness is of vital importance for such an ultralight aircraft. Composites are being widely and increasingly used in the aerospace industry because of their advantages that include the high specific strength and stiffness over traditional metallic materials. Besides, composites have the potential for absorbing the energy in a crash event. The crashworthiness of the cockpit section is analyzed in this paper and some modifications in the subfloor have been made to improve the survivability of the pilot. Advances in commercial softwares have enabled engineers to simulate crash events. The three-dimensional structure model is established by use of CATIA software and the crash process is simulated by MSC/DYTRAN. By comparing the crashworthiness of composite structures, reliable basis is provided for the design of a safe and sound structure.